Profiling of Translatomes of in Vivo–Grown Pollen Tubes Reveals Genes with Roles in Micropylar Guidance during Pollination in Arabidopsis . Issue 2 (14th February 2014) - Lin, Shih-Yun; Chen, Pei-Wei; Chuang, Ming-Hsiang; Juntawong, Piyada; Bailey-Serres, Julia; Jauh, Guang-Yuh
Abstract : This work described the use of a method for the specific isolation of ribosome-associated mRNAs of in vivo–grown pollen tubes to identify over 500 genes with transcripts highly enriched or specific to in vivo–grown pollen tubes. T-DNA insertion alleles of a number of these genes conferred defects in late stages of the pollination process by haploid gametes. Abstract: Transcriptome profiling has been used to identify genes expressed in pollen tubes elongating in vitro; however, little is known of the transcriptome of in vivo–grown pollen tubes due to the difficulty of collecting pollen that is elongating within the solid maternal gynoecium. Using a pollen-specific promoter ( ProLAT52 ) to generate epitope-tagged polysomal-RNA complexes that could be affinity purified, we obtained mRNAs undergoing translation (the translatome) of in vivo–grown pollen tubes from self-pollinated gynoecia of Arabidopsis thaliana . Translatomes of pollen grains as well as in vivo– and in vitro–cultured pollen tubes were assayed by microarray analyses, revealing over 500 transcripts specifically enriched in in vivo–elongating pollen tubes. Functional analyses of several in vivo mutants ( iv ) of these pollination-enhanced transcripts revealed partial pollination/fertilization and seed formation defects in siliques ( iv2, iv4, and iv6 ). Cytological observation confirmed the involvement of these genes in specialized processes including micropylar guidance ( IV6 and IV4 ), pollen tube burst ( IV2 ), and repulsion of multiple pollen tubes in embryo sac ( IV2 ). In summary, the selective immunopurification of transcripts engaged with polysomes in pollen tubes within self-fertilized florets has identified a cohort of pollination-enriched transcripts that facilitated the identification of genes important in in vivo pollen tube biology.